Analytical Approach for Modeling of Multi Well CO2 Injection. (July 2017) - Robinson, Morgan; Leonenko, Yuri
Abstract: Disposal of carbon dioxide (CO2 ) into underground geological formations is considered a viable strategy for the mitigation of global warming. It aims to reduce greenhouse gases emitted from point sources such as power plants. In order to select and evaluate a potential storage formation, many reservoir properties such as porosity, permeability, lateral and vertical extents, and a variety of residual fluid properties are considered. Injection design, which includes the placement of injectors and their flow rates, should be chosen to optimize injection capacity. One of the most important considerations to be addressed during design stage of sequestration is evaluation of pressure behaviour inside the reservoir during and after injection as the sequestered CO2 increases the pressure within the formation. In order to maintain the integrity of the reservoir the pressure needs to be maintained below the fracture pressure, typically at least 10% below. Thus evaluation of reservoir pressure is essential to ensure the reservoir remains under the maximum allowable pressure while sequestering the maximum amount of CO2 for long term storage in the reservoir. The optimal injection rates within a multi well injection site occur when the bottom-hole pressure at each injection site is at the maximum allowable pressure. In this study we present an analytical approach for modeling the pressure evolution during multi well CO2 injection into saline aquifers and using the model modify the injection rates to optimize injection capacity within a formation. We show that this optimization procedure significantly increases the capacity of formation as opposed to using the same injection rate at each wellbore.